2011
DOI: 10.1037/a0025443
|View full text |Cite
|
Sign up to set email alerts
|

Spillover to triadic and dyadic systems in families with young children.

Abstract: Research has evidenced support for the spillover model, which asserts that parents' marital functioning influences their parenting and coparenting behavior in dyadic (mother-child and father-child) and triadic (mother-father-child) family contexts. However, few studies have simultaneously investigated the spillover model in both parenting and coparenting systems, preventing examination of whether spillover impacts both systems equally or differentially. Further, little research has examined whether quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
110
4
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(138 citation statements)
references
References 50 publications
15
110
4
9
Order By: Relevance
“…The present findings partially support the spillover hypothesis which suggests that negative interparent relationship is likely to affect parental-child relationship negatively (Stroud et al 2011;Whiteside-Mansell et al 2009). A large number of studies on spillover effects show that parental negative attitudes and behaviors toward children resulting from interparent relational problems have negative effects on children's lifespan development, including psychological distress (Shelton and Harold 2008), emotional adjustment , social skill development (Whiteside-Mansell et al 2009) and academic achievement in school (Sturge-Apple et al 2010).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The present findings partially support the spillover hypothesis which suggests that negative interparent relationship is likely to affect parental-child relationship negatively (Stroud et al 2011;Whiteside-Mansell et al 2009). A large number of studies on spillover effects show that parental negative attitudes and behaviors toward children resulting from interparent relational problems have negative effects on children's lifespan development, including psychological distress (Shelton and Harold 2008), emotional adjustment , social skill development (Whiteside-Mansell et al 2009) and academic achievement in school (Sturge-Apple et al 2010).…”
Section: Discussionsupporting
confidence: 86%
“…The spillover model suggests that negative emotions and behaviors experienced and displayed during spousal conflict can spillover into parenting behavior and negatively affect child-parent relationship and child development (Benson et al 2008;Bradford et al 2004;Buehler et al 2006;Krishnakumar et al 2003;Stroud et al 2011;Whiteside-Mansell et al 2009). Parents who display aggression toward their spouse may be in increasing risk of displaying the same behavior toward their children, which may make children vulnerable to behavior problems (Almeida et al 1999;Bradford et al 2004;Buehler et al 2006;Harold and Conger 1997).…”
Section: Introductionmentioning
confidence: 97%
“…Marital dissatisfaction, in contrast, may lead to mothers feeling more stressed by their childcare responsibilities (Goldberg & Easterbrooks, 1984), which may increase the possibility that the stressed mothers would use harsh discipline with their children. This finding suggested that unlike in American contexts where fathering may be more influenced by their marital relationship (Coiro & Emery, 1998;Cummings et al, 2010;Davies et al, 2009;Stroud et al, 2011), in Chinese contexts, mothering may be more likely determined by the state of the marital relationship than fathering. That is, although there is some research with Western samples supporting fathering-vulnerability hypothesis (Cummings et al, 2010;Davies et al, 2009;Stroud et al, 2011), the present research provided at least some support for the mothering-vulnerability hypothesis in Chinese societies.…”
Section: Discussionmentioning
confidence: 79%
“…According to this perspective, the associations between marital satisfaction and harsh discipline may be different for mothers and fathers. Indeed, in the few studies that investigated the spillover effects between marital relationship and parent-child relationship, it was found that negative marital relations had stronger effects on father-child relationships than on mother-child relationships, supporting fathering-vulnerability hypothesis (Cummings, Merrilees, & George, 2010;Davies, Sturge-Apple, Woitach, & Cummings, 2009;Stroud, Durbin, Wilson, & Mendelson, 2011). Given the theoretical hypothesis and empirical findings, it is possible that unsatisfying marital relationship may be more likely to lead the fathers who experienced parenting stress to use harsh discipline compared to the mothers with similar experiences.…”
Section: Parent Gender Differences In the Moderating Mechanismmentioning
confidence: 89%
“…According to family systems perspective, problems in the marital subsystem can spillover into the parenting subsystem and thereby influence children (Stroud, Durbin, Wilson, & Mendelsohn, 2011), although the marital subsystem has at least some unique contribution over the parenting subsystem (Crockenberg et al, 2007;Finger, Hans, Bernstein, & Cox, 2009). Thus, it is possible that in our study, to some extent, the effects of marital problems on children's emotion regulation and defense mechanisms were mediated through the quality of parenting.…”
Section: Discussionmentioning
confidence: 99%